Business Retention and Expansion (BRE) Programs: Approaches to BRE Programs - Henry M. Cothran (EDIS)
FE-652, a 3-page fact sheet by Henry M. Cothran, is the second in a series of ten on establishing Business Retention and Expansion (BRE) programs. It describes two broad approaches to BRE -- traditional, or "volunteer", and continuous, or "paid staff." Includes references. Published by the UF Department of Food and Resource Economics, September 2006.